Studi Numerik Optimasi Propeller Kapal Selam 29 meter Dengan Menggunakan High Skew - Cahya Kusuma; I Made Ariana (Universitas Muhammadiyah Sidoarjo, 2017)
Indonesia is an archipelagic nation and most shallow water channel in Western Indonesia, making the concept of mini submarine use by the Navy to be the right choice. One of the most important engineering is to design a mini submarine propeller with a high level of optimization. This research method is based on the result of numerical simulation using Computer Fluid Dynamic (CFD) which use B-series as base with skew variation 36o, 45o, 54o. It is expected that the results of this research can provide solutions in the selection of efficient design propeller for mini submarine 29m. With the open water diagrams generated then obtained the greatest efficiency value on B4-522 with skew obtained at 45 ° skew angle. The optimum velocity value is at J = 0.07 at 8.9 knots with an efficiency value of 0.856.